PENERAPAN PENDEKATAN SAVI UNTUK MENINGKATKAN HASIL BELAJAR DAN SIKAP PERCAYA DIRI SISWA PADA MATERI JUAL BELI SISWA KELAS III SDN CORENDA (Penelitian Tindakan Kelas di SDN Corenda Kecamatan Cisitu Kabupaten Sumedang Tahun Ajaran 2016/2017) - ISTIQOMAH, IIS; Hanifah, Nurdinah; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2017)
Early data showed that 23 students from 36 students from third grade Corenda Elementary School as subject research still not yet reached the target. Beside that 12 out 36 students still struggles with self-confidence learning. Caused by less of media variation and the selection of learning approach wthich not emphasized the differences of learning type student. Researcher wanna solved the problem with applying SAVI approach. Researcher used kuantitative research method and kualitative spiral model classroom action research started with planning, immplementation, observation, and reflection. Improved porved by the observation at planning step, first cycles (83,3%), second cycles (100%). Implementation of teacher activity at first cycles (87,9%), second cycles (100%). Students activity at first cycles (68,2%), and second cycles (82,7%). Result learning at first cycles (58,3%) and second cycles (86,1%). Self-confidence’s student at first cycles (58,8%), and second cycles (89,1%). Therefore, by applying SAVI approached, result learning and self-confidence Corenda Elementary School students Cisitu Subdistriction Sumedang Regency had improved.